Invitro determination of alpha amylase inhibitory activity of two selected medicinal plants extracts - Liyanaarachchi, L.V.V.; Rathnayake, H.M.A.L.; Wijesundara, W.M.A.G.U.I.; Sivasinthujah, S.; Manoranjan, T. (University of Sri Jayewardenepura, 2023)
Background: Pancreatic α-amylase inhibitors offer an effective strategy to reduce postprandial hyperglycemia in the management of diabetes mellitus. In this study, two medicinal plants; Trianthema decandra and Thespesia populnea were subjected to determine the α- amylase inhibitory activity. Though the alpha amylase activity of these above-mentioned plants has been investigated in different countries, the level of alpha amylase activity presence in these plants has not been investigated so far in Sri Lanka. Objective: To determine the in vitro alpha amylase inhibitory activity of T.decandra and T.populnea leaves extracts using porcine pancreatic α- amylase enzyme. Methods & Materials: The leaves of T.decandra and T.populnea were collected from Jaffna, dried under shade, ground to a powder. The extractions were prepared by maceration with methanol, acetone and petroleum ether. Subsequently, α-amylase inhibitory assay was performed separately on the leaf extracts of T. decandra and T. populnea by employing acarbose as the standard compound. The IC50 values for the extracts were calculated from the respective assay. The statistical significance was evaluated by the analysis of variance (ANOVA) followed by Tukey’s test. Results: The IC50 values of leaf of methanol, acetone, petroleum ether extracts were 44.34±2.3 μg/ml, 346.6±4.5 μg/ml, 674.9±2.7μg/ml. Methanol, acetone and petroleum ether leaf extracts of T. decandra showed IC50 values of 175.93±4.04 μg/ml, 447.6±1.3 μg/ml, and 1020.3±3.2 μg/ml. The methanol extract of T. populnea showed significantly α-amylase inhibition comparable to the acarbose (IC50 = 83.85±2.64 μg/ml) (p>0.05). None of the petroleum ether extracts showed alpha amylase inhibitory activity. Conclusion: The findings revealed that methanolic extract of T.populnea leaf extract exhibited α – amylase inhibitory activity which could be used for further screening of specific bioactive compounds that might responsible for their α amylase inhibitory activity.